P19 Vitamin D in the Prevention of Acute Respiratory Infection: A Systematic Review of Clinical Studies. (19th November 2012) - Jolliffe, DA; Martineau, AR; Griffiths, CJ
Abstract : Introduction and Objectives: Acute respiratory infections (ARI) cause significant morbidity and mortality: in the UK, during 2004, 33, 957 deaths occurred due to pneumonia alone. Vitamin D metabolites enhance immunity to a wide range of respiratory pathogens in vitro, and numerous clinical studies have investigated whether vitamin D deficiency is a risk factor for ARI, or whether vitamin D supplementation prevents ARI. Systematic reviews of this literature are lacking, however. Our objective was to conduct a systematic review of clinical studies investigating the relationship between vitamin D status or the effect of vitamin D supplementation on risk of ARI. Methods: The PubMed database was searched on 7th June 2012 using the terms 'vitamin D' and' respiratory infection'. Cross-sectional studies, case-control studies, cohort studies or clinical trials in human subjects investigating the relationship between serum concentration of vitamin D metabolites or the effect of vitamin D supplementation on risk of ARI were included; ARI was defined as any infection of the respiratory tract with symptom duration of 30days or less. Studies relating exclusively to tuberculosis were excluded, as this is classically regarded as a chronic respiratory tract infection, with symptom duration usually exceeding 30 days. Results: Thirty-one studies reporting data from a total of 43, 272 participants were included in our review. Of these, 19 were observational studies (3 cross-sectional, 8 case-control and 8 cohort)and 12 were randomised controlled trials. Sixteen of the 19 observational studies reviewed reported statistically significant associations between vitamin D deficiency and susceptibility to ARI, and 3 reported no such association. Six of the 12 clinical trials reviewed reported protective effects of vitamin D against ARI, while five reported null effects, and one reported an adverse effect on pneumonia recurrence. Conclusions: Observational studies report consistent associations between vitamin D deficiency and susceptibility to ARI in a wide range of age-groups in diverse clinical settings. By contrast, randomised controlled trials of vitamin D supplementation for the prevention of ARI report conflicting results, possibly reflecting varying prevalence of vitamin D deficiency in study populations and/or heterogeneity in vitamin D supplementation regimens investigated.